The impact of latent tuberculosis screening programmes for migrant populations in high income, low burden countries - Alice E. Taylor; Eisin McDonald; Hazel Henderson; Peter MacPherson (PLoS ONE, 2025)
Background Migrants from high to low tuberculosis (TB) incidence countries may benefit from screening for latent TB infection (LTBI), but the optimal approaches and effectiveness are not well described. Methods Our primary objective was to synthesise evidence for cost-effectiveness, and barriers and facilitators to successful implementation, of LTBI screening programmes for migrants entering high income, low TB burden countries. Evidence was synthesised using rapid review methodologies. Results 41 studies (including 2 reviews) were included, covering the European region and national programmes. Main settings of LTBI screening were primary care, new arrivals clinics, and schools. The most frequently cited facilitator was structural cohesiveness (integration of health care services, collaboration with community partnerships, and co-ordination of care with social workers or accommodation staff). The most frequently cited barrier was lack of understanding and misconceptions of service users. Economic evaluations consistently demonstrated long term cost-savings for LTBI programmes. Screening migrants from countries of origin of the highest TB burden is more cost-effective but less likely to identify all TB and ultimately eliminate TB compared to screening at a lower TB burden threshold. Conclusions We found consistent evidence that LTBI screening programmes for migrants from high to low tuberculosis TB incidence countries can be effective and cost-saving in a variety of settings. A co-ordinated, integrated approach is a key programme facilitator.